Artificial Intelligence and Digital Entrepreneurship: Opportunities and Challenges - الساعاتي ثناء عبدالكريم عبدالرحيم; الساعاتي سفير عبدالكريم عبدالرحيم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Artificial intelligence mechanisms are moving in light of the digital transformation that the world is witnessing in the use of modern technologies as a means of organizing and creating new and innovative projects. The digital transformation has led to the emergence of a new concept branching from entrepreneurship under the title "digital entrepreneurship." The current study aims to shed light on the concept and mechanisms of artificial intelligence as a means of accelerating innovation and establishing digital projects. It is a vital tool in identifying economic trends, confronting economic crises, and supporting sustainable development goals. Therefore, the current study seeks to clarify the concept of artificial intelligence and digital transformation technologies and to identify the most important opportunities and challenges facing digital entrepreneurship, as the (swot) method was used and the strengths and weaknesses were identified, which allows for the creation of integrated visions about the strategies that contribute to enhancing business flexibility and creating a climate for leadership and creativity through the use of modern technology and automation techniques as a tool for competition in the lab or market. Using the analytical approach of previous studies, the study provides recommendations related to the need to achieve effective integration between artificial intelligence applications and the digital entrepreneurship sector, enhance the digital infrastructure of projects, improve organizational performance, and spread the culture of digital technologies as a means of driving a sustainable economy.